Low-temperature synthesis of carbon nanotubes via floating catalyst-chemical vapor deposition method - Atiyah, Mahmood Rashid (2010)
Carbon nanotubes (CNTs) are widely synthesized at high temperatures via floating catalyst chemical vapor deposition (FC-CVD) method. It is important to reduce the synthesis temperature of CNTs to allow better control of the reactor’s conditions, and to eliminate the formation of carbon by-products as well as reduce the overall cost. Therefore, the main objectives of this work were (i) to synthesize carbon nanotubes at low temperatures using some improvements to the CVD technique, (ii) to investigate the effects of temperature on the synthesis of CNTs and (iii) to simulate the temperature and velocity profile of the FC-CVD system in the absence of reaction.